A Synonymous Variant c.579A>G in the ETFDH Gene Caused Exon Skipping in a Patient With Late-Onset Multiple Acyl-CoA Dehydrogenase Deficiency: A Case Report - Hu, Guorui; Zeng, Jingxia; Wang, Chunli; Zhou, Wei; Jia, Zhanjun; Yang, Jun; Zheng, Bixia (Frontiers in Pediatrics, 2020)
Background: Multiple acyl-CoA dehydrogenase deficiency (MADD) is an autosomal recessive disorder characterized by a wide range of clinical features, including muscle weakness, hypoglycemia, metabolic acidosis and multisystem dysfunctions. Loss-of-function mutations in the electron transfer flavoprotein dehydrogenase (ETFDH) gene are associated with MADD. Disease-causing synonymous variants in the ETFDH gene have not been reported so far. Methods: We reported the clinical course of a Chinese girl who was diagnosed with late-onset MADD by the whole exome sequencing. The effects of variants on mRNA splicing were analyzed through transcript analysis in vivo and minigene splice assay in vitro. Results: The 6-month-old girl initially showed muscle weakness, muscular hypotonia, mild myogenic damage and fatty liver. The blood and urine metabolic screening by tandem mass spectrometry suggested MADD. Molecular analysis of ETFDH gene revealed two novel heterozygous variants, a frameshift mutation c.1812delG (p.V605Yfs*34) in exon 13 and a synonymous variant c.579A>G (p.E193E) in exon 5. The transcript analysis in vivo exhibited that the synonymous variant c.579A>G caused exon 5 skipping. The minigene splice assay in vitro confirmed the alteration of ETFDH mRNA splicing which could lead to the production of a truncated protein. Supplementation of riboflavin, carnitine and low-fat diet improved the clinical symptoms. Conclusion: We firstly report a rare case of MADD with a pathogenic synonymous variant in the ETFDH gene which highlights the importance and necessity of bioinformatic analysis and functional testing for synonymous variants when searching for causative gene mutations. The results expand the spectrum of pathogenic variants in MADD.